The birth bed: A qualitative study on the views of midwives regarding the use of the bed in the birth space. Issue 1 (February 2016) - Townsend, B.; Fenwick, J.; Thomson, V.; Foureur, M.
Abstract: Background: There is a growing body of evidence to show that the birth environment can influence women's experiences of labour and birth as well as midwifery practice. A common feature of the modern birth space is the bed. Knowledge about how the use of the bed shapes clinicians' perceptions and attitudes is limited. Aim: The aim of this paper is to describe midwives' perceptions of the birth bed. Method: Qualitative descriptive design. Fourteen midwives from one Queensland maternity unit participated in digitally recorded and transcribed interviews. Thematic analysis was used to analyse the data set. Findings: Four themes were identified. The first, described beliefs that using the bed formed part of women's childbirth expectations. A second theme, captured midwives' perceptions that the bed was also an object required to safely undertake their work. The third theme described how others commonly worked to ensure the woman stayed off the bed. Lastly, there was evidence that whilst wanting to avoid the use of the bed, some were reluctant, fearing potential reprimand. Conclusion: The themes highlight differences in how the midwives conceptualised the use of a bed within a birth space. While some avoided the use of the bed altogether others would only conceive of women moving off the bed if everything was 'normal'. How the bed was culturally constructed appeared to dictate clinical practice. Reflecting on the meaning of an object, such as the bed, is important if clinicians are to fully understand how the birth environment influences their practice and thus women's experiences of labour and birth.